Probability density distribution of instantaneous values of a speech signal in Polish - BRACHMAŃSKI, Stefan P.; MAJEWSKI, Wojciech (Archives of Acoustics, 1979)
In the present paper the results of investigating the probability density distribution of instantaneous values of a Polish speech signal are presented. The aim was to obtain data providing an additional criterion for the generation of artificial test signals. The signals are used in objective methods of measuring the quality of Polish speech transmission. The probability density distribution of instantaneous values of a speech signal in Polish was compared with the distributions in English, German, and Russian. The minimum duration of an acoustic signal, sufficient to obtain stationary characteristics of the probability density distribution of instantaneous values of a Polish speech signal, was determined. The distributions obtained were approximated by means of exponential functions.